Antibacterial and antifungal activity of various extracts of Bacopa monnieri - M. K. K., Fazlul; S.P, Deepthi; Mohammed, Irfan; Farzana, Y.; Munira, B.; M.H.M, Nazmul (Advanced Scientific Research, 2019)
Bacopa monnieri was also known as “Brahmi.” Theses plant has been considered as medicinal plants in Ayurvedic systems for centuries. This present study was carried out to evaluate the antibacterial and antifungal properties of ethanolic, diethyl ether, ethyl acetate, and aqueous extracts of B. monnieri. Agar disc diffusion tests were carried out to determine the antimicrobial effects of ethanolic, diethyl ether, ethyl acetate and aqueous extracts of B. monnieri against Gram-positive (Staphylococcus aureus ATCC 25923), Gram-negative (Escherichia coli ATCC 25922) bacterial strains and antifungal strains (Aspergillus flavus, and Candida albicans). Among the various extracts, diethyl ether extracts of B. monnieri has an antibacterial potency against Staphylococcus aureus (gram positive), and ethyl acetate extract showed effects on E. coli (gram negative) at higher concentrations of 300 µg mL-1. The ethanolic extract has potent antifungal activity against the fungus (Aspergillus flavus, and Candida albicans) compared to diethyl ether and ethyl acetate-ether. Both extracts (diethyl ether and ethyl acetate) has a minimum antifungal effect while these extracts showed more inhibitory effects on tested bacteria. Inhibitory effects of the aqueous extract were not observed at all concentration (100 µg mL-1, 200 µg mL-1and 300 µg mL-1) against the entire examined bacterial and fungal species. The finding of this study indicates the antibacterial and antifungal activity exhibited by the ethanolic, diethyl ether, and ethyl acetate extract of B. monnieri can be validated to the management of medicinal plant throughout the world.